Impact of COVID-19 Pandemic in the Urban People of Kathmandu Valley (Voice of Teacher, 2022)
COVID-19 is a pandemic of an acute respiratory syndrome that emerging in Wuhan, China in December 2019 spread and affected to the various parts of the world in short period of time. This study explores the social, economic and social psychological impact of COVID-19 in people from different professions and family backgrounds of various categories of urban people. Similarly, I used exploratory research design by taking 5 respondents from different backgrounds and occupations purposively for case study. I found that COVID-19 pandemic has made a huge loss to all economic sectors, employer as well as employee. It creates fear, tension, anxiety and depression in the people. Likewise, this pandemic has also brought changes in the sanitary behavior of the urban people. Moreover, people used to maintain social relationship through cell phone, messenger call and telephone rather than direct meeting and gathering. The nature and degree of impact of COVID-19 was different in the sampled respondents except similar changes in sanitary habit.